Risk factors for de Quervain's disease in a French working population - Audrey Petit Le Manac'h; Yves Roquelaure; Catherine Ha; Julie Bodin; Geraldine Meyer; Frederic Bigot; Martin Veaudor; Alexis Descatha; Marcel Goldberg; Ellen Imbernon (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: De Quervain's disease (DQD) is a significant cause of musculoskeletal pain among workers. The aim of this study was to assess the relative importance of personal and occupational risk factors for DQD in a working population. METHODS: A total of 3710 workers from a French region were randomly included in the cross-sectional study between 2002-2005. There were 45 subjects with DQD (of these, 5 subjects had a bilateral condition), diagnosed by 83 trained occupational physicians performing a standardized physical examination. Individual factors and work exposure were assessed by a standardized physical and a self-administered questionnaire. Statistical associations between DQD and individual and occupational factors were analyzed using logistic regression modeling in the whole sample and among women. RESULTS: The prevalence rates of uni- or bilateral DQD for the whole, male and female working populations were 1.2% [95% confidence interval (95% CI) 0.9-1.6], 0.6% (95% CI 0.3-0.9) and 2.1% (95% CI 1.4-2.8), respectively. Personal risk factors for DQD were mainly age (1.1 for 1-year increase in age) and female gender [odds ratio (OR) 4.9, 95% CI 2.4-10.1]. Work-related factors were workpace dependent on (i) technical organization (OR 2.0, 95% CI 1.0-4.0), (ii) repeated or sustained wrist bending in extreme posture (OR 2.6, 95% CI 1.3-5.3) and (iii) repeated movements associated with the twisting or driving of screws (OR 3.4, 95% CI 1.7-7.1). No association was found with psychosocial factors. CONCLUSIONS: Personal and work-related factors were associated with DQD in the working population; wrist bending and movements associated with the twisting or driving of screws were the most significant of the work-related factors.